IoT-Based Semi Automatic Water Control for Bucket Catfish Farming: Sistem Pengendalian Air Semi-Otomatis Berbasis IoT untuk Budidaya Ikan Lele dalam Bak - A’rasy Fahruddin; Adi Irawan (Indonesian Journal of Innovation Studies, 2025)
General Background Catfish cultivation is a major freshwater aquaculture activity widely practiced in Indonesia, particularly in urban areas with limited land availability. Specific Background The bucket-based aquaculture system (budidamber) provides a compact solution, yet requires frequent water quality monitoring and maintenance. Knowledge Gap Manual water control often leads to delayed maintenance due to farmers’ time constraints, reducing water quality and affecting fish survival. Aims This study aims to design and implement a semi-automatic IoT-based system for monitoring and controlling water quality in bucket catfish cultivation. Results The system utilizes ESP32, temperature sensor DS18B20, ultrasonic sensor, and Telegram-based control, achieving an average water temperature of 28.9°C within the acceptable standard range and enabling automated water drainage with an average delay of 11 seconds and deviation of 4%. Novelty The integration of real-time monitoring, automated drainage scheduling, and remote control via Telegram provides a practical semi-automatic solution for small-scale aquaculture. Implications This system supports efficient time management for farmers and improves water quality control, contributing to sustainable small-scale aquaculture practices in limited-space environments. Keywords: Internet of Things, Budidamber, Water Quality Monitoring, ESP32, Aquaculture System Key Findings Highlights Remote monitoring system maintains stable water conditions within standard limits Automated drainage operates with minor delay under real conditions Integrated messaging control simplifies operational management for farmers